2022
DOI: 10.3389/fvets.2022.1057686
|View full text |Cite
|
Sign up to set email alerts
|

Molecular survey of Zika virus in the animal-human interface in traditional farming

Abstract: Backyard animal husbandry is common in rural communities in developing countries and, given the conditions in which it occurs, it can increase the risk of disease transmission, such as arboviruses. To determine the presence of the Zika virus (ZIKV) and abundance of its arthropod vectors we evaluated the socioeconomic implications involved in its transmission in two highly vulnerable Mayan communities in the state of Yucatan that practice backyard farming. An analytical cross-sectional study was carried out thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…We suggested this threat because pigs are native host and reservoir for other flaviviruses like classical swine fever virus, atypical porcine pestivirus, and zoonotic Japanese encephalitis virus. Afterward, studies from other groups showed evidence of Zika virus infection in pigs on farms in Mexico and in mosquitoes collected inside pigpens [ 35 , 36 ]. Experimental intravenous injection of two pregnant pigs with Zika virus did not result in transplacental and fetal infections.…”
Section: Discussionmentioning
confidence: 99%
“…We suggested this threat because pigs are native host and reservoir for other flaviviruses like classical swine fever virus, atypical porcine pestivirus, and zoonotic Japanese encephalitis virus. Afterward, studies from other groups showed evidence of Zika virus infection in pigs on farms in Mexico and in mosquitoes collected inside pigpens [ 35 , 36 ]. Experimental intravenous injection of two pregnant pigs with Zika virus did not result in transplacental and fetal infections.…”
Section: Discussionmentioning
confidence: 99%